(untitled) (Research, Society and Development, 2022)
This integrative literature review aimed to analyze the findings about the SARS-CoV-2 action on the male genital tract. The database used in the search was PubMed, Scielo and Google Scholar with the following descriptors: “Male fertility”, “COVID-19”, “Infertility”, in addition to the use of the Boolean operator (AND). The final sample was 25 baseline studies. The entry of the coronavirus takes place through the interaction of its proteins with ACE-2 and TMPRSS2. Such proteins were identified in the male reproductive system, which explains several clinical findings in patients who were infected. This interaction of the virus with cells prevents the formation of Ang 1-7, which has anti-inflammatory properties, so its reduction would cause local tissue damage in the testicular tissue. Such findings ranged from histological changes with the formation of an inflammatory infiltrate to possible autoimmune orchitis. In addition, there are controversies on certain topics, such as the carriage of the virus in semen and its potential to cause embryological damage. The study showed the different pathophysiological possibilities of the virus in causing changes in male fertility, through the inflammatory effect, direct cytopathological action of the virus, fever, infections of other structures of the reproductive system, direct alterations in the hypothalamic pituitary axis and use of drugs as a treatment. All these results show the complexity of this virus in other systems and its mechanisms, which requires further studies for its full understanding.